Biology and survival of extremely halophilic archaeon Haloarcula marismortui RR12 isolated from Mumbai salterns, India in response to salinity stress - Thombre, Rebecca S. (Sci Rep, 2016)
Haloarchaea are unique microorganism’s resistant to environmental and osmotic stresses and thrive in their habitats despite extreme fluctuating salinities. In the present study, haloarchaea were isolated from hypersaline thalossohaline salterns of Bhandup, Mumbai, India and were identified as Haloferax prahovense, Haloferax alexandrines, Haloferax lucentense, Haloarcula tradensis, Haloarcula marismortui and Haloarcula argentinensis. The mechanism of adaptation to contrasting salinities (1.5 M and 4.5 M) was investigated in the extreme haloarchaeon, Hal. marismortui RR12. Hal. marismortui RR12 increased the intracellular sequestration of K(+) and Cl(−) ions in hypo salinity and hyper salinity respectively as detected by Energy-dispersive X-ray spectroscopy microanalysis (EDAX) and Inductively Coupled Plasma- atomic Emission Spectroscopy (ICP-AES) indicating the presence of ‘salt-in’ strategy of osmoadaptation. As a cellular response to salinity stress, it produced small heat shock like proteins (sHSP) identified using MALDI-TOF MS and increased the production of protective red carotenoid pigment. This is the first report on the study of the concomitant cellular, molecular and physiological mechanism adapted by Hal. marismortui RR12 when exposed to contrasting salinities in external environment.